2006
DOI: 10.2174/156802606778249810
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Reuptake Inhibitors: The Corner Stone in Treatment of Depression for Half a Century – A Medicinal Chemistry Survey

Abstract: Inhibition of serotonin (5-HT) reuptake has been a central theme in the therapy of depression for half a century. Through the years these therapies have improved, particularly with regard to side effects, and today's selective serotonin reuptake inhibitors (SSRIs) constitute a reasonably effective offer for the patients. However, there is still room for major improvement and considering that almost 20% of the population in the western world will experience a depressive period in their lifetime, there is a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 103 publications
0
30
0
Order By: Relevance
“…These endeavors have provided a plethora of ligands for these transporters, including compounds with high affinity and selectivity for each of the three transporters ( Table 3). The tricyclic antidepressants (TCAs), including imipramine and clomipramine, were developed in the 1950s as the first generation of monoamine transporter drugs (Moltzen and Bang-Andersen, 2006;Andersen et al, 2009a). However, the TCAs display activity across a variety of different receptors (Gillman, 2007), and new generations of monoamine transporter inhibitors with little or no affinity for other proteins have subsequently been developed.…”
Section: Ligands For the Monoamine Transportersmentioning
confidence: 99%
“…These endeavors have provided a plethora of ligands for these transporters, including compounds with high affinity and selectivity for each of the three transporters ( Table 3). The tricyclic antidepressants (TCAs), including imipramine and clomipramine, were developed in the 1950s as the first generation of monoamine transporter drugs (Moltzen and Bang-Andersen, 2006;Andersen et al, 2009a). However, the TCAs display activity across a variety of different receptors (Gillman, 2007), and new generations of monoamine transporter inhibitors with little or no affinity for other proteins have subsequently been developed.…”
Section: Ligands For the Monoamine Transportersmentioning
confidence: 99%
“…Neuroprotective compounds that can slow down disease progression with few side effects have been studied for treating HD. For example, selective serotonin reuptake inhibitors (SSRIs), a class of drugs that is widely used for the treatment of patients with depression and severe anxiety disorders, have been shown to increase BDNF expression (19,20) and stimulate neurogenesis responsive to BDNF. Duan et al (21)(22)(23) have demonstrated that several SSRI compounds, including paroxetine and sertraline, elicited beneficial effects in HD mice.…”
Section: Huntington Disease (Hd)mentioning
confidence: 99%
“…Selective serotonin reuptake inhibitors (SSRIs), a class of drugs that is widely used for the treatment of patients with depression and severe anxiety disorders, has been shown to increase BDNF expression in brain (Nibuya et al, 1995;Nibuya et al, 1996;Moltzen and Bang-Andersen, 2006). SSRIs can also stimulate neurogenesis and protect neurons against metabolic/oxidative insults and processes known to be responsive to BDNF (Malberg and Blendy, 2005).…”
Section: Introductionmentioning
confidence: 99%